2014
DOI: 10.1155/2014/186508
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Cardiovascular Development Related Genes in Stem Cells Isolated from Deciduous Pulp and Adipose Tissue

Abstract: Human exfoliated deciduous teeth (SHED) and adipose stem cells (ASC) were suggested as alternative cell choice for cardiac regeneration. However, the true functionability of these cells toward cardiac regeneration is yet to be discovered. Hence, this study was carried out to investigate the innate biological properties of these cell sources toward cardiac regeneration. Both cells exhibited indistinguishable MSCs characteristics. Human stem cell transcription factor arrays were used to screen expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The differentiated cells were morphologically similar to in vivo cardiomyocytes and expressed abundantly cardiomyocyte-specific markers, both at the mRNA and protein level. Similar to this study, an earlier study reported that the dental stem cells from deciduous pulp could differentiate into cardiomyocytes in vitro under activin A and BMP2 induction protocol 11.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The differentiated cells were morphologically similar to in vivo cardiomyocytes and expressed abundantly cardiomyocyte-specific markers, both at the mRNA and protein level. Similar to this study, an earlier study reported that the dental stem cells from deciduous pulp could differentiate into cardiomyocytes in vitro under activin A and BMP2 induction protocol 11.…”
Section: Discussionsupporting
confidence: 87%
“…Similar morphological changes were reported in other studies describing the cardiomyogenic differentiation of stem cells by chemical induction 11-17, 29, 30. The cells differentiated by SAHA induction showed abundant expression of cardiomyocyte-specific markers, such as α-SMA, TNNT2, Desmin, and ACTC1, at both mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, a comparative study revealed that adMSC expressed significantly more cardiomyocyte specific biomarkers as DFSCs following cardiac programming with cytokine supplemented culture medium [11]. The impact of MSC origin on programming capability was also shown for non-cardiac cell lineages like hepatocytes and smooth muscle cells [59,62].…”
Section: Discussionmentioning
confidence: 87%
“…In recent years, MSC have also been utilized for the generation of mesenchymal as well as non-mesenchymal cell lineages, including neuron-like, hepatocyte-like, and cardiac-like cells [6][7][8][9][10]. Despite these promising results, the differentiation of human MSC into fully mature cardiomyocytes bearing all their respective phenotypical and functional characteristics is difficult [11][12][13][14][15]. As MSC are located in various tissues, they represent a heterogeneous progenitor cell population dependent on the tissue source and the individual donor [16].…”
Section: Introductionmentioning
confidence: 99%